Informatsionnaia programma . Informatsionnaia programma . Informational Program . Информационная программа - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The program analyzes Bill Clinton's three months in power. Featured in the program: Zorin, Valentin Sergeevich (Journalist) Contributors: Sukhoi, Vladimir (Anchor) Передача о 3-х месяцах нахождения у власти Билла Клинтона. В программе участвуют: Зорин, Валентин Сергеевич (Журналист) Создатели: Сухой, Владимир (Ведущий/Ведущая)